System architecture for network-attached FPGAs in the cloud using partial reconfiguration - Ringlein, Burkhard; Abel, Francois; Ditter, Alexander; Weiss, Beat; Hagleitner, Christoph; Fey, Dietmar (Proceedings - 29th International Conference on Field-Programmable Logic and Applications, FPL 2019, 2019)
Emerging applications such as deep neural networks, bioinformatics or video encoding impose a high computing pressure on the Cloud. Reconfigurable technologies like Field-Programmable Gate Arrays (FPGAs) can handle such compute-intensive workloads in an efficient and performant way. To seamlessly incorporate FPGAs into existing Cloud environments and leverage their full power efficiency, FPGAs should be directly attached to the data center network and operate independent of power-hungry CPUs. This raises new questions about resource management, application deployment and network integrity. We present a system architecture for managing a large number of network-attached FPGAs in an efficient, flexible and scalable way. To ensure the integrity of the infrastructure, we use partial reconfiguration to separate the non-privileged user logic from the privileged system logic. To create a really scalable and agile cloud service, the management of all resources builds on the Representational State Transfer (REST) concept.
CRIS-Team Scopus Importer:2019-12-10
Keywords: Cloud computing; Data centers; Network-attached FPGA; Partial reconfiguration; Stand-alone FPGA